Understanding and accessibility of pre-and proto-historical research issues : sites, museums and communication strategies : proceedings of the XVIII UISPP World Congress (4-9 June 2018, Paris, France). - Delfino, Davide, 1976-; Nizzo, Valentino, (UISPP proceedings series ;, 2021)
Museums are increasingly seen as the place where scientific research and heritage education meet; 8 papers here consider the mediation of language from research usage to public usage, making a museum visit an educational experience, universal accessibility, local community involvement, and use of media and new technologies for public outreach.